2012
DOI: 10.5539/jps.v1n2p180
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Anatomical Analyses of the Serpentine Ecotype of Adenophora triphylla var. japonica (Campanulaceae)

Abstract: The morphological and anatomical analyses of leaves in the serpentine ecotype of Adenophora triphylla var. japonica (Regel) H. Hara were carried out. In comparison to the normal type of this variety, the serpentine ecotype has a narrower leaf due to decrease in the number and size of cells. The stenophyllization process of the serpentine ecotype is similar to that of the rheophytic ecotype. The study further indicates that the decreased number and size of cells is a general tendency in stenophyllization. By co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 16 publications
3
15
0
Order By: Relevance
“…japonica. Therefore, the stomatal number per leaf of the serpentine ecotype was lower than that of the normal type of this species [17], which is consistent with our results of decreased stomatal number per leaf in serpentine areas.…”
Section: Referencessupporting
confidence: 92%
See 1 more Smart Citation
“…japonica. Therefore, the stomatal number per leaf of the serpentine ecotype was lower than that of the normal type of this species [17], which is consistent with our results of decreased stomatal number per leaf in serpentine areas.…”
Section: Referencessupporting
confidence: 92%
“…This finding suggests that this stomatal type developed for adaptation to dry environments. Similarly, [17] reported that the stomatal size and density of the serpentine ecotype of Adenophora…”
Section: Resultsmentioning
confidence: 88%
“…Our study, along with [11,12], indicated that A. triphylla var. japonica can be categorised into serpentine, rheophytic, and coastal ecotypes in addition to the normal type.…”
Section: Discussionsupporting
confidence: 56%
“…The serpentine ecotype of A. triphylla var. japonica also had narrow leaves, but the leaf thickness and stomatal density was significantly different from those of the normal plants, suggesting that there were different adaptation processes between the two ecotypes of this species [12]. From these studies, it appears that A. triphylla var.…”
Section: Introductionmentioning
confidence: 84%
“…The origin or the introduction events of KP and WP are not found in published literature. In the present study, the species of WP and KP were confirmed as H. verticillata and A. triphylla, respectively (Ohga et al, 2012;USDA, 2018). It can be speculated that WP and KP were introduced to Sri Lanka from East Asia; however, further studies are needed for the confirmation.…”
supporting
confidence: 62%